2022
DOI: 10.1101/2022.12.21.521461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Weight loss improves skeletal muscle mitochondrial energy efficiency

Abstract: Weight loss is associated with a disproportionate decrease in whole-body energy expenditure that may contribute to the heightened risk for weight-regain. Evidence suggests that this energetic mismatch originates from lean tissue. Although this phenomenon is well documented, the mechanisms have remained elusive. We hypothesized that increased mitochondrial energy efficiency in skeletal muscle is associated with reduced expenditure under weight loss. Wildtype male C57BL6/N mice were fed with high-fat diet for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…Lastly, in regard to mitochondrial content, there were no significant changes in mitochondrial content in skeletal muscle from HFD-fed mice or primary myotubes derived from severely obese and insulin resistant humans as indicated by several protein markers. These results are consistent with several previous studies with the similar duration of HFD intervention or human muscle cell culture model [ [44] , [45] , [46] , [47] , [48] ], but conflict with a couple studies where either longer period of HFD intervention was applied or myotubes from T2D humans were studied [ 44 , 49 ]. Taken together, it suggests that mitochondrial content does not change until later in the development of insulin resistance and T2D.…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, in regard to mitochondrial content, there were no significant changes in mitochondrial content in skeletal muscle from HFD-fed mice or primary myotubes derived from severely obese and insulin resistant humans as indicated by several protein markers. These results are consistent with several previous studies with the similar duration of HFD intervention or human muscle cell culture model [ [44] , [45] , [46] , [47] , [48] ], but conflict with a couple studies where either longer period of HFD intervention was applied or myotubes from T2D humans were studied [ 44 , 49 ]. Taken together, it suggests that mitochondrial content does not change until later in the development of insulin resistance and T2D.…”
Section: Discussionsupporting
confidence: 90%
“…Prola et al demonstrated that reduced CL coincides with lower muscle P/O, and reconstitution of mitochondrial CL with unilamellar vesicles can restore P/O [30]. In our previous study, we demonstrated that weight loss also increases TLCL and CL transacylase tafazzin [27]. In that study, we also demonstrated that global tafazzin knockdown decreases muscle P/O and increases systemic metabolic rate.…”
Section: Discussionsupporting
confidence: 63%
“…PmFB were prepared as previously described [27]. Briefly, a small portion of freshly dissected red GAS muscle was placed in buffer X [7.23 mM K 2 EGTA, 2.77 mM Ca K 2 EGTA, 20 mM imidazole, 20 mM taurine, 5.7 mM ATP, 14.3 mM phosphocreatine, 6.56 mM MgCl 2 ·6H 2 O, and 50 mM 2-(N-Morpholino) ethanesulfonic acid potassium salt (K-MES) (pH7.4)].…”
Section: Methodsmentioning
confidence: 99%